기상조건 및 온습도지수가 젖소의 유질에 미치는 영향 - 양인정; 한광우; 윤호백; 이준희; 이원재; 전상곤; 김진욱; In Jeong Yang; Kwang Woo Han; Ho Baek Yoon; Jun Hee Lee; Won Jae Lee; et al. (농업생명과학연구, 2013)
지구 온난화에 따른 외기온도의 지속적인 상승은 젖소의 유질저하를 초래하는 것으로 알려져 있다. 현재 우리나라에서는 원유의 유지방함량, 체세포수 및 세균수를 기준으로 유대가격을 산정하고 있어 궁극적으로 여름철 온도의 상승은 젖소농가의 수익성에 악영향을 미치게 된다. 본 연구에서는 경북지역을 중심으로 외기온도와 상대습도을 조사하고 외기온도와 상대습도에 따른 온습도지수 (THI)를 도출하여 유질에 미치는 영향을 상관관계와 회귀분석 방법을 이용하여 분석하였다. 유지방 함량은 겨울철 4.0-4.1%에서 여름철로 접어들면서 3.6-3.7%로 저하하였고 동시에 온도와 THI가 상승하였다. 체세포수 1등급 출현율은 4-9월이 다른 달에 비해 낮은 것으로 나타났다. THI는 유지방 함량과는 r=-0.8914, 체세포수 1등급 출현율과는 r=-0.6067의 상관관계를 보였으나, 세균수 1등급 출현율과는 통계적으로 유의한 상관관계을 보이지 않았다. THI에 따른 유지방함량 및 체세포수 1등급 출현율을 예측할 수 있는 공식을 단순회귀분석법을 이용하여 도출하였다. 본 연구의 결과을 종합하면, 온도 및 상대습도를 이용하여 도출한 THI는 젖소의 고온스트레스를 분석하는 지표로 사용될 수 있을 것으로 사료된다. Increasing in ambient temperature by global warming is likely to reduce milk yields and negatively affect milk quality in dairy cows. The projected increase in temperature would impact on dairy industry since production costs would increase with reductions in milk production. In Korea, dairy farmers are paid according to the composition of the raw milk components (milk fat concentrations, somatic cell counts and bacteria cell counts). In this study, to assess changes of milk quality caused by ambient temperature and relative humidity in the southern part of Korea (Gyeongbuk province), the temperature-humidity index (THI) was calculated on the base of the equation suggested by Schoen's model. Correlation and regression analysis were performed to determine the effects of the temperature, relative humidity and THI on milk quality. Increased temperature and THI significantly reduced milk fat concentrations from 4.0-4.1% during the winter to 3.6-3.7% during the summer. Occurrence ratio of the 1st grade somatic cell counts (1st SCC) was lower during April to September compared to that of annual average. The THI was negatively correlated to milk fat concentrations (r=-0.8914) and 1st SCC (r=-0.6067) in the overall Gyeongbuk region. There were significant effects of the temperature and THI on milk fat concentrations and 1st SCC. Whereas occurrence ratio of 1A bacteria cell counts (1A BC) had no correlation with the temperature, relative humidity and THI. To make predictions for milk fat concentrations and 1st SCC, the regression model was developed to fit data. Overall, these results suggest that the THI is a useful and easy way to assess the risks of heat stress and is a candidate parameter to predict milk quality.